2022
DOI: 10.3390/microorganisms10101909
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Staphylococcal Biofilm on the Surface of Implants in Orthopedic Infection

Abstract: Despite advanced implant sterilization and aseptic surgical techniques, implant-associated infection remains a major challenge for orthopedic surgeries. The subject of bacterial biofilms is receiving increasing attention, probably as a result of the wide acknowledgement of the ubiquity of biofilms in the clinical environment, as well as the extreme difficulty in eradicating them. Biofilm can be defined as a structured microbial community of cells that are attached to a substratum and embedded in a matrix of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 167 publications
0
13
0
Order By: Relevance
“…Of note, S. aureus growth itself was not affected by the metal concentrations, suggesting that it might form biofilms in PJIs. ,, PJIs occur in up to 4% of revision arthroplasties . It was reported that the presence of a foreign body and local metal release reduce the infectivity dose of S.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, S. aureus growth itself was not affected by the metal concentrations, suggesting that it might form biofilms in PJIs. ,, PJIs occur in up to 4% of revision arthroplasties . It was reported that the presence of a foreign body and local metal release reduce the infectivity dose of S.…”
Section: Discussionmentioning
confidence: 98%
“…The vast majority of nosocomial infections involved a biofilm-producing organism [ 2 ]. Thus, the development of strategies that limit biofilm development by using modified biomaterials or permitting the dissociation of already-formed biofilms in order to avoid material removal constitute urgent clinical needs in situations of economic or clinical relevance [ 53 ].…”
Section: Biofilm Formation and Clinical Significancementioning
confidence: 99%
“…However, implant-associated infection (IAI) is a catastrophic complication of orthopedic surgery. 1 According to statistics, the incidence of IAI ranges from 1 to 30%. 2 Tubercular IAI (TB-IAI) is a rare infection caused by the Mycobacterium tuberculosis complex (MTBC), constituting approximately 0.14% of the cases of tuberculosis (TB).…”
Section: Introductionmentioning
confidence: 99%